The Role of GMOs in Trade Disputes - Andrew Schmitz; Charles Moss; Won Koo (EDIS, 2004)
GMOs in agricultural products have met with consumer resistance both domestically and abroad, resulting in marketing and policies that could disrupt trade and international negotiations. Research presented during the conference focused on three areas: (1) technical aspects of GMOs and their international impacts, (2) property rights surrounding GMOs and identity preservation costs associated with keeping marketing channels segmented, and (3) consumer education related to GMOs. This is EDIS document FE471, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published December 2003.